On A Method for the Numerical Solution of Integro-Differential Equations - Kobelkov, Г.М. (Bulletin of L.N. Gumilyov Eurasian National University. Mathematics, computer science, mechanics series, 2018)
The article is devoted to a new method for the numerical solution of integro-differential and integral equations, consisting in the fact that the solution of the corresponding linear algebraic systems is carried out using an iterative method, in which the analogue of the integral operator is taken from the bottom layer and the differential one from the top layer.